MDR1 Gene Polymorphisms Are Associated with Glucocorticoid-Induced Avascular Necrosis of the Femoral Head in a Chinese Population - Xue, Yun (Mary Ann Liebert, Inc., 2014)
P-glycoprotein (P-gp) is present in various tissue cells, required for the pumping of lipophilic drugs (including glucocorticoids) out of cells. We hypothesized that polymorphisms in the P-gp encoding gene (multidrug-resistant transporter-1 [MDR1]) are related to individual differences in glucocorticoid sensitivity and the development of glucocorticoid-induced avascular necrosis of the femoral head (GANFH). In this case–control study, we genotyped three known single-nucleotide polymorphisms (SNPs: C1236T, G2677T/A, and C3435T) within the MDR1 gene in 662 Chinese subjects. Statistically significant differences between GANFH patients and either healthy controls or glucocorticoid-resistant patients (non-GANFH) were found for the T allele or TT genotype of C3435T. The haplotype TTT, composed of these three SNPs, exhibited a significant association with the disease. No associations were identified between C1236T or G2677T/A and GANFH. Our results suggest that the C3435T polymorphism of the MDR1 gene is associated with susceptibility to GANFH in a Chinese population.